Siglec-H-Deficient Mice Show Enhanced Type I IFN Responses, but Do Not Develop Autoimmunity After Influenza or LCMV Infections - Szumilas, Nadine; Corneth, Odilia B. J.; Lehmann, Christian H. K.; Schmitt, Heike; Cunz, Svenia; Cullen, Jolie G.; Chu, Talyn; Marosan, Anita; Mócsai, Attila; Benes, Vladimir; Zehn, Dietmar; Dudziak, Diana; et al. (Frontiers in Immunology, 2021)
Siglec-H is a DAP12-associated receptor on plasmacytoid dendritic cells (pDCs) and microglia. Siglec-H inhibits TLR9-induced IFN- production by pDCs. Previously, it was found that Siglec-H-deficient mice develop a lupus-like severe autoimmune disease after persistent murine cytomegalovirus (mCMV) infection. This was due to enhanced type I interferon responses, including IFN-. Here we examined, whether other virus infections can also induce autoimmunity in Siglec-H-deficient mice. To this end we infected Siglec-H-deficient mice with influenza virus or with Lymphocytic Choriomeningitis virus (LCMV) clone 13. With both types of viruses we did not observe induction of autoimmune disease in Siglec-H-deficient mice. This can be explained by the fact that both types of viruses are ssRNA viruses that engage TLR7, rather than TLR9. Also, Influenza causes an acute infection that is rapidly cleared and the chronicity of LCMV clone 13 may not be sufficient and may rather suppress pDC functions. Siglec-H inhibited exclusively TLR-9 driven type I interferon responses, but did not affect type II or type III interferon production by pDCs. Siglec-H-deficient pDCs showed impaired Hck expression, which is a Src-family kinase expressed in myeloid cells, and downmodulation of the chemokine receptor CCR9, that has important functions for pDCs. Accordingly, Siglec-H-deficient pDCs showed impaired migration towards the CCR9 ligand CCL25. Furthermore, autoimmune-related genes such as Klk1 and DNase1l3 are downregulated in Siglec-H-deficient pDCs as well. From these findings we conclude that Siglec-H controls TLR-9-dependent, but not TLR-7 dependend inflammatory responses after virus infections and regulates chemokine responsiveness of pDCs.